Characterizations of ethosuximide-loaded bismuth ferrite nanoparticles for the potential treatment of epilepsy - ULAĞ, SONGÜL (My University, 2023)
Epilepsy is the most common neurological disease that affected people of all ages, races, social classes, and geographical locations. According to the 2019 World Health Organization (WHO) data, about 0.7 % of the population is struggling with epilepsy. In addition, nearly 5 million people are diagnosed every year. The basic characteristic of epilepsy is aberrant electrical activity in several brain regions. About %70 patients with epilepsy can be treated successfully with antiepileptic drugs to control the patient's seizures. 20–30% of patients exhibit pharmacoresistance, and only a small portion of these patients will benefit from surgical intervention. Therefore, developing a successful treatment for the disease is still quite difficult. To accomplish this objective, antiepileptic drug-loaded carrier nanoparticles can be an alternative treatment for epilepsy.Recent developments to improve the release of drugs from smart materials include Near Infrared Light (NIR) radiation (NIR), ultraviolet (UV) and visible wavelength light, magnetic fields, ultrasound, and electrical stimulation. Compared to drug delivery systems based on stable passive delivery, these strategies offer more effective control over the delivery of drugs. Nanoparticle drug carriers are being studied further for controlled drug delivery due to their benefits including good structure and tunable characteristics. Multiferroic materials due to their controllable possession, have drawn interest in recent years to develop new materials or structures. Bismuth ferrite (BiFeO3, BFO) is a single-phase multiferroic material with a polar R3c space group and rhombohedral distorted cell, has the ability to be both ferroelectric and antiferromagnetic.In this study, bare and drug loaded bismuth ferrite nanoparticles were synthesized by coprecipitation method. Bare and drug loaded nanoparticles were characterized by fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), X-ray diffraction analysis (XRD), and scanning electron microscopy (SEM). Ethosuximide is an FDA-approved, made available as an efficient and generally well-tolerated medication to treat absence seizures. It prevents clonic seizures generated on by bicuculline or pentylenetetrazole when administered subcutaneously. Also, biological test was done by using microglia cells.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); Epilepsy; bismuth ferrite nanoparticles; ethosuximide; joint infections; tissue engineering